Self-assembled photoadditives in polyester films allow stop and go chemical release - Cheng, Ting (2017)
Near-infrared (NIR) triggered chemical delivery allows on-demand release with the advantage of external tissue stimulation. Bioresorbable polyester poly-L-lactic acid (PLLA) was compounded with photoadditives of neat zinc oxide (ZnO) nanoparticles and 980  365 nm LiYF4:Tm3+, Yb3+ upconverting nanoparticles (UCNP). Subsequently, neat ZnO and UCNP blended PLLA films of sub-50 m thickness were knife casted with a hydrophobic small molecule drug mimic, fluorescein diacetate. The PLLA films displayed a 500 times increase in fluorescein diacetate release from the 50 mW NIR irradiated PLLA/photoadditive film compared to non-irradiated PLLA control films. Larger ratios of UCNP/neat ZnO increased photocatalysis efficiency at low NIR duty cycles. The synergistic increase results from the self-assembled photoadditives of neat zinc oxide and upconverting nanoparticles (UCNPs), as seen in transmission electron microscopy. Colloidal ZnO, which does not self-assemble with UCNPs, had less than half the release kinetics of the self-assembled PLLA films under similar conditions, advocating Förster resonance energy transfer as the mechanism responsible for the synergistic increase. Alternative to intensity modulation, pulse width modulation (duty cycles from 0.1 to 1) of the low intensity 50 mW NIR laser diode allowed tailorable release rates from 0.01 to 1.4 % per day. With the low intensity NIR activation, tailorable release rates, and favourable biocompatibility of the constituents, implanted PLLA photoadditive thin films could allow feedback mediated chemical delivery.